Canadian Muslims and Canada’s domestic and foreign policy issues: an analysis - Islam, Syed Serajul; Hossain, Ishtiaq (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2012)
This paper analyses the participation of Canadian Muslims in debates affecting Canada‘s domestic and foreign policy issues. Here, the Canadian Muslim identity is first of all briefly spelled out. Then a detailed discussion is made of their role in debates affecting the country‘s domestic affairs. Next, the Canadian foreign policy issues which are of interest to Canadian Muslims are identified and their stand on those issues are analysed. The discussion in this paper demonstrates that the Muslim citizens of Canada are conscious of their own Canadian Muslim identity. It also shows that like other Canadians, the Muslim citizens of Canada express their opinion freely on matters, which are of importance to the country. Although their impact on policy-making remains negligible, their increasing participation in the political process of the country beacons hope for their more lasting impact on the country‘s public policy-making in future.